2014
DOI: 10.18632/oncotarget.1882
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation of Alk induces neonatal lethality in knock-in AlkF1178L mice

Abstract: The ALK (Anaplastic Lymphoma Kinase) gene encodes a tyrosine kinase receptor preferentially expressed in the central and peripheral nervous systems. A syndromic presentation associating congenital neuroblastoma with severe encephalopathy and an abnormal shape of the brainstem has been described in patients harbouring de novo germline F1174V and F1245V ALK mutations. Here, we investigated the phenotype of knock-in (KI) mice bearing the AlkF1178L mutation (F1174L in human). Although heterozygous KI mice did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…85 Characterization of heterozygous KI Alk F1178L mice indicated that these mice did not phenocopy the severe neurological disorders, including major feeding and breathing difficulties, observed in the syndromic patients with de novo germline F1245V and F1174V activating ALK mutations. 86 However, we noticed a high lethality of homozygotes between 24 and 48 hr after birth. Evaluation of basic physiological functions 12 hr after birth uncovered a dramatic reduced milk intake for KI Alk F1178L homozygotes, 86 which appears closely related to the feeding difficulties that characterized the patients with encephalopathy.…”
Section: Murine and Zebrafish Nb Models: From Tools To Understand Nb mentioning
confidence: 64%
See 2 more Smart Citations
“…85 Characterization of heterozygous KI Alk F1178L mice indicated that these mice did not phenocopy the severe neurological disorders, including major feeding and breathing difficulties, observed in the syndromic patients with de novo germline F1245V and F1174V activating ALK mutations. 86 However, we noticed a high lethality of homozygotes between 24 and 48 hr after birth. Evaluation of basic physiological functions 12 hr after birth uncovered a dramatic reduced milk intake for KI Alk F1178L homozygotes, 86 which appears closely related to the feeding difficulties that characterized the patients with encephalopathy.…”
Section: Murine and Zebrafish Nb Models: From Tools To Understand Nb mentioning
confidence: 64%
“…Interestingly, Alk activation in sympathetic nervous system ganglia induced opposite effects compared to the ones reported in Ret −/− mice . Characterization of heterozygous KI Alk F1178L mice indicated that these mice did not phenocopy the severe neurological disorders, including major feeding and breathing difficulties, observed in the syndromic patients with de novo germline F1245V and F1174V activating ALK mutations . However, we noticed a high lethality of homozygotes between 24 and 48 hr after birth.…”
Section: Murine and Zebrafish Nb Models: From Tools To Understand Nb mentioning
confidence: 72%
See 1 more Smart Citation
“…The Anaplastic lymphoma kinase (ALK) gene, originally identified as part of the chimeric nucleophosmin-ALK (NPM-ALK) protein in a chromosomal rearrangement associated with anaplastic large cell lymphoma [ 228 ], maps to chromosome 2p23 and encodes a tyrosine kinase receptor normally expressed at high levels in developing central and peripheral nervous systems districts, such as thalamic nuclei, spinal cord motoneurons and sympathetic, enteric ganglia and motor nuclei of the brainstem [ 229 , 230 , 231 , 232 ]. Its expression has been detected in sympathetic neuroblasts at E12.5 and E13.5 [ 44 ] and it seems to act by inducing neurogenesis in sympathetic ganglia [ 233 , 234 ].…”
Section: Key Transcription Factors and Target Genes In Neuroblastomamentioning
confidence: 99%
“…Unlike many of the IRK subfamily members, the normal physiological function of ALK is yet to be fully elucidated. There is evidence that ALK plays a role in growth and fetal development of both the central nervous system (CNS) and peripheral nervous system (PNS) [119,120,[122][123][124][125][126][127][128][129]. Furthermore, evidence indicates that constitutively active mutated ALK proteins induce neuronal growth and differentiation [130,131].…”
Section: Anaplastic Lymphoma Kinase (Alk)mentioning
confidence: 99%